THE MALADIES OF CUSHING SYNDROME - Tan, Jie En; Tan, Florence Hui Sieng; Kuan, Yueh Chien; Chan, Pei Lin (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODOUCTION/BACKGROUND Ectopic ACTH secretion (EAS) occurs in 1.6-6% of cases of small-cell lung carcinoma (SCLC). Diagnosis can be challenging due to a wide variety of clinical manifestations. CASE A 58-year-old male smoker presented with acute respiratory distress. He had a 2-month history of worsening dyspnoea, generalized oedema and reduced effort tolerance. At presentation, he was tachypnoeic with an oxygen saturation of 90%, blood pressure of 187/94 mm Hg and heart rate of 103 beats/minute. Examination revealed bilateral lung crepitations with generalized pitting oedema. A CXR showed multiple ill-defined lung masses with pulmonary infiltrates. Laboratory results revealed hypokalaemia (potassium 2.4 mmol/L) with metabolic alkalosis (pH 7.58, HCO 46.9). A CT TAP was consistent with lung malignancy with lymphangitis, carcinomatosis and bone and liver metastases. He was oxygen-dependent and had persistent hyperglycaemia (HbA1c 7.7%) and hypertension with hypokalaemia requiring >3 antihypertensive agents. Despite not being cushingoid-looking and with no hyperpigmentation, ectopic CS was suspected and confirmed with grossly elevated cortisol (>1740 nmol/L) and ACTH level 57.1 pmol/L (1.6- 13.9), non-suppressible by high dose dexamethasone suppression test (cortisol >1750 nmol/L, ACTH 57.9 pmol/L). Lung biopsy confirmed SCLC. Spironolactone and ketoconazole were started, with improvement in BP and metabolic parameters. Cortisol level reduced to 352 nmol/L within 3 weeks of treatment. He was planned for palliative chemotherapy but desaturated further. Therapeutic anticoagulant, IV piperacillintazobactam and Pneumocystis pneumonia (PCP) treatment with clindamycin and primaquine were added. PCR for PCP returned as positive later. Due to his poor ECOG score, family opted for conservative treatment and he succumbed later on palliative care. CONCLUSION Presence of profound hypokalaemia, hypertension with oedema and new-onset diabetes with lung malignancy should alert the clinicians to possible EAS. The intense hypercortisolism in EAS requires prompt treatment to reduce hypercortisolism and targeted therapy for associated co-morbidities. Early diagnosis is important as EAS confers poorer prognosis to SCLC and is associated with more extensive disease and reduced response to firstline treatment.